Gain-of-function mutations in Caenorhabditis elegans levamisole-sensitive nicotinic receptors evaluated at the single-channel level - Bergé, Ignacio (2025)
The nematode Caenorhabditis elegans is a valuable model for studying both human neuromuscular disorders and parasitic nematodes. Notably, it expresses one of the largest families of nicotinic acetylcholine receptors (nAChRs), pentameric ligand-gated ion channels that mediate synaptic transmission. At the neuromuscular junction, the primary excitatory receptor is the levamisole-sensitive AChR (L-AChR). We investigated gain-of-function mutations in the L-AChR pore-lining TM2 domain, some of which mimic those causing human slow-channel congenital myasthenic syndromes (CMS). Using null mutants lacking essential subunits UNC-38 or UNC-29, we reintroduced these subunits carrying specific mutations and performed single-channel recordings from C. elegans cultured muscle cells. Wild-type receptors display brief, isolated openings, whereas TM2 9′ mutants exhibit prolonged openings and extended activation episodes, underscoring the conserved functional role of this position across species. Additional mutations in other TM2 residues linked to human CMS similarly increase channel open time, recapitulating pathological gating behavior observed in patients. Quinidine sulfate, a therapeutic agent used to treat slow-channel CMS, reduced the abnormally prolonged channel openings of mutant L-AChRs. These findings demonstrate the evolutionary conservation of TM2 residues in nAChR activation, validate C. elegans as a model for human channelopathies, and support its use in exploring therapeutic interventions for nAChR-related disorders.